Penyusunan Modul Ajar Kurikulum Merdeka Untuk Tingkat SMK: Id - Amiruddin; Muhammad Hasim; Aminuddin; Akmal Hidayat; Nurlaela (V-MACHINE: Vocational and Mechanical Community Service Journal, 2024)
The development of teaching modules aligned with the Merdeka curriculum for junior and senior high schools is essential to improving the quality of education. Several studies have highlighted the importance of supporting teachers in creating teaching modules based on the Merdeka curriculum to address the challenges faced by educators who may not fully understand the concepts and techniques required. These studies emphasize the importance of training sessions and workshops to equip teachers with the skills needed to develop effective teaching modules that are aligned with the principles of the Merdeka curriculum. In addition, integrating 21st-century skills into teaching modules is essential to prepare students for the challenges of the modern era. The Merdeka curriculum emphasizes the freedom to design learning experiences that are tailored to students' needs and encourage deeper understanding of the material. It also encourages the use of innovative approaches, such as problem-based learning, to enhance the effectiveness of teaching modules. In addition, mathematics teachers' readiness to implement the Merdeka curriculum was assessed as positive, indicating a willingness to embrace a new educational paradigm. However, challenges remain, such as the need for further support in developing instructional materials that are aligned with the thematic nature of the Merdeka curriculum. The development of teaching modules that are aligned with the Merdeka curriculum is an important aspect of modern education. By providing teachers with the necessary training and resources, schools can ensure that students receive high-quality education that is aligned with the principles of the Merdeka curriculum.